Paradoxical embolism caused by totally implantable venous access port: a case report and literature review - Zonghong Han; Zhongming He; Wenhua Chen; Qi Wang (Frontiers in Cardiovascular Medicine)
Totally implantable venous access ports (TIVAPs) are commonly used for patients undergoing chemotherapy and long-term repeated infusions. The incidence of thrombosis is low and rarely leads to serious complications. We report a case of right atrial thrombosis and paradoxical embolism in a 58-year-old male with atrial fibrillation (AF) and patent foramen ovale (PFO) 28 months after TIVAP implantation. The patient presented with dizziness and left limb weakness, subsequent diagnostic imaging revealed right temporal lobe infarction and a mass in the right atrium, who eventually recovered and was discharged after cardiac surgery and anticoagulation. This case highlights the rare but severe complication of right atrial thrombosis associated with TIVAP, particularly in patients with AF and PFO. Proper placement and timely removal of totally implantable venous access ports are crucial to minimize complications. Further research is needed to determine the necessity of anti-coagulation and PFO screening in patients with AF receiving central venous catheters.